Autonomous Learning under Study: An Annotated Bibliography from Two Studies with Different Approaches - Doni Marzuki (Politeknik Negeri Padang, 2013)
The concept of autonomous learning has gained massive attention in educational research and practice over the last three decades. This concept is regarded as an option in this modern educational world (Scharle & Szabo, 2000) which demands more active participation and less teacher- dependence of learners. In the area of language learning, many researchers have put attention to this concept in order to get more understanding of the theory and practice. Two approaches are commonly used by researchers in this autonomous learning matter are qualitative and quantitative. These two approaches are discussed in this paper in order to get good comparison of advantages and weaknesses to be used for research in autonomous learning area. A mix approach or a combination approach between qualitative and quantitative is also discussed in this paper to get more ideas and understanding about the alternative way of conducting the research in this area.